Prescription Patterns in Dialysis Patients: Differences Between Hemodialysis and Peritoneal Dialysis Patients and Opportunities for Deprescription. (April 2020) - Marin, Judith G.; Beresford, Laura; Lo, Clifford; Pai, Alexander; Espino-Hernandez, Gabriela; Beaulieu, Monica
Background: Patients treated with maintenance dialysis are at high risk of polypharmacy given their many comorbidities as well as complications from their disease state and treatment. The prescribing patterns and burden of polypharmacy in patients treated with maintenance dialysis, and specifically the difference between hemodialysis (HD) and peritoneal dialysis (PD) prescribing, are not well characterized. Objectives: The objectives of this study were to review the prescribing patterns for patients treated with maintenance dialysis, to compare prescribing pattern between HD and PD, and to identify opportunities for deprescription. Design: This is a retrospective cohort study. Setting: This study was conducted in all dialysis centers in British Columbia, Canada. Patients: Patients who were receiving chronic dialysis (>120 days on the same dialysis modality) between June 3 and October 1, 2015, and registered in the British Columbia (BC) Renal Patient Records and Outcomes Management Information System. Measurements: Patient demographics as well as both prescription and non-prescription medications were collected. Comparison of discrete and continuous variables was made by chi-square analysis and independent t test, respectively. All statistical tests were 2-sided, and a P value of <.05 was considered statistically significant. Methods: Medications were classified by indication: (1) management of renal complications, (2) cardiovascular (CV) medications, (3) diabetes medications, or (4) management of symptoms, and then classified as to whether they were a "potentially inappropriate medication" (PIM) or not. Ethics approval was granted from the University of British Columbia Research and Ethics Board. Results: In total, 3017 patients met inclusion criteria (2243 HD, 774 PD). The mean age was 66.2 ± 14.8 years. The HD group had more patients over 80 years old (22.1% vs 12.5%) and more patients with diabetes and CV disease. The mean number (standard deviation [SD]) of discrete prescribed medications was 17.71 (5.72) overall with more medications in the HD group versus the PD group. The mean number of medications increased with dialysis vintage in both groups. HD patients were on more medications for renal complications and management of symptoms than PD patients. Of the total number of medications prescribed, 5.02 (2.78) were classified as a PIM, with the number of PIMs higher in HD vs PD patients: 5.37 (2.83) versus 4.02 (2.37). Limitations: In BC, some of the medications are prescribed through standardized protocols and may not be comparable with other Canadian provinces. We report here prescribing patterns, not utilization patterns, as we are not able to ascertain actual consumption of prescribed medication. Conclusion: This study reviews and characterizes both the prescription and non-prescription medication prescribed to HD patients and PD patients in BC. Pill burden in both groups is high, as is the prescription of PIMs. Patients receiving maintenance HD receive more overall medications and more PIMs. These results highlight areas of opportunities for future systematic and patient-informed deprescription initiatives in both patient groups.